Corporate Purpose and Employee Sustainability Behaviors - C. B. Bhattacharya; Sankar Sen; Laura Marie Edinger-Schons; Michael Neureiter (Journal of Business Ethics, 2022)
This paper examines the effects of employees' sense that they work for a purpose-driven company on their workplace sustainability behaviors. Conceptualizing corporate purpose as an overarching, relevant, shared ethical vision of why a company exists and where it needs to go, we argue that it is particularly suited for driving employee sustainability behaviors, which are more ethically complex than the types of employee ethical behaviors typically examined by prior research. Through four studies, two involving the actual employees of construction companies, we demonstrate that purpose drives the sustainability behaviors of employees by causing them to take psychological ownership of sustainability. In addition, we show that the sustainability-enhancing effect of purpose is stronger when employees perceive that they have higher autonomy in enacting their sustainability actions and for those employees for whom being moral is more central to their sense of self.
Keywords: 300; Corporate purpose; Employee sustainability behaviors; Sustainability ownership; Job autonomy; Moral identity centrality